Les genres décrits n° 3 - Julie Abbou; Cécile Ropiteaux; Karine Dorvaux; Hortense Colère (Glad!)
In this issue, our Chronicle « Describing Gender » goes back to school. How do feminist teachers invest language (and metalanguage) and how do they teach language to prevent the spreading of a sexist grammar ?